Mutations reveal voltage gating of CNGA1 channels in saturating cGMP - Martínez-François, Juan Ramón (The Rockefeller University Press, 2009)
Activity of cyclic nucleotide–gated (CNG) cation channels underlies signal transduction in vertebrate visual receptors. These highly specialized receptor channels open when they bind cyclic GMP (cGMP). Here, we find that certain mutations restricted to the region around the ion selectivity filter render the channels essentially fully voltage gated, in such a manner that the channels remain mostly closed at physiological voltages, even in the presence of saturating concentrations of cGMP. This voltage-dependent gating resembles the selectivity filter-based mechanism seen in KcsA K(+) channels, not the S4-based mechanism of voltage-gated K(+) channels. Mutations that render CNG channels gated by voltage loosen the attachment of the selectivity filter to its surrounding structure, thereby shifting the channel's gating equilibrium toward closed conformations. Significant pore opening in mutant channels occurs only when positive voltages drive the pore from a low-probability open conformation toward a second open conformation to increase the channels' open probability. Thus, the structure surrounding the selectivity filter has evolved to (nearly completely) suppress the expression of inherent voltage-dependent gating of CNGA1, ensuring that the binding of cGMP by itself suffices to open the channels at physiological voltages.